KRITIK GOLDZIHER DAN SCHACHT TERHADAP AUTENTISITAS HADIS SERTA RESPONS ULAMA HADIS - Mafiqah Kayyisah; Romlah Abubakar Askar; Miftahuddin Miftahuddin (Hikmah: Journal of Islamic Studies, 2026)
AbstractThis study examines the Orientalist critique of hadith authority through the thoughts of Ignaz Goldziher and Joseph Schacht and compares it with the responses of hadith scholars. Using a qualitative library research method, this article analyzes the main arguments of Goldziher and Schacht alongside the methodological responses developed in classical and contemporary hadith scholarship. The findings show that Goldziher’s critique tends to generalize hadith as a reflection of later Muslim social, political, and theological conflicts without sufficiently examining the internal mechanisms of hadith transmission. Meanwhile, Schacht’s argument is problematic because it relies heavily on early fiqh literature to assess hadith authenticity and assumes that the absence of a hadith in legal discussions indicates its non-existence. In contrast, hadith scholars developed a systematic method of verification through sanad and matan criticism. Sanad criticism evaluates the continuity of transmission and the reliability of transmitters, while matan criticism examines textual coherence, conformity with stronger evidence, and consistency with established religious principles. This study concludes that Orientalist criticism is useful for encouraging historical awareness in hadith studies, but its methodological limitations must be assessed critically through the established tools of hadith scholarship.ABSTRAKPenelitian ini mengkaji kritik orientalis terhadap otoritas hadis melalui pemikiran Ignaz Goldziher dan Joseph Schacht serta membandingkannya dengan respons ulama hadis. Dengan menggunakan metode kualitatif berbasis penelitian kepustakaan, artikel ini menganalisis argumen utama Goldziher dan Schacht serta respons metodologis yang dikembangkan dalam tradisi ilmu hadis klasik dan kontemporer. Hasil penelitian menunjukkan bahwa kritik Goldziher cenderung menggeneralisasi hadis sebagai cerminan konflik sosial, politik, dan teologis umat Islam pasca-Nabi tanpa cukup mempertimbangkan mekanisme internal transmisi hadis. Sementara itu, argumen Schacht bermasalah karena terlalu bertumpu pada literatur fikih awal untuk menilai autentisitas hadis dan mengasumsikan bahwa ketiadaan hadis dalam diskusi hukum tertentu menunjukkan bahwa hadis tersebut belum ada. Sebaliknya, ulama hadis telah mengembangkan metode verifikasi yang sistematis melalui kritik sanad dan matan. Kritik sanad menilai kesinambungan periwayatan dan kredibilitas perawi, sedangkan kritik matan menguji koherensi teks, kesesuaiannya dengan dalil yang lebih kuat, serta konsistensinya dengan prinsip-prinsip agama. Penelitian ini menyimpulkan bahwa kritik orientalis berguna untuk mendorong kesadaran historis dalam studi hadis, tetapi keterbatasan metodologisnya harus dinilai secara kritis melalui perangkat ilmu hadis yang telah mapan.